2022
DOI: 10.14740/gr1483
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Acute Gastrointestinal Bleeding in Patients With COVID-19: A Case-Control Study

Abstract: Background: Coronavirus disease 2019 (COVID-19) patients are at higher risk of acute gastrointestinal bleeding (AGIB) due to higher use of steroids, mechanical ventilation, and use of anticoagulation. We performed this study to compare outcomes of AGIB in COVID-19-positive patients and those without COVID-19 and AGIB.Methods: This was a case-control study including patients admitted from March 2020 to February 2021 with the diagnosis of AGIB. Patients were divided into two groups: COVID-19-positive and non-COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Importantly, recent studies have shown that patients hospitalized with coronavirus disease 2019 (COVID-19) are at risk of a gastrointestinal (GI) bleed [2][3][4]. The reported incidence of GI bleeds was 2-3% in hospitalized patients with COVID-19 and was noted to be higher in ICU patients [3,[5][6]. The widespread use of anticoagulation and corticosteroids in these patients could lead to a significant GI bleed [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, recent studies have shown that patients hospitalized with coronavirus disease 2019 (COVID-19) are at risk of a gastrointestinal (GI) bleed [2][3][4]. The reported incidence of GI bleeds was 2-3% in hospitalized patients with COVID-19 and was noted to be higher in ICU patients [3,[5][6]. The widespread use of anticoagulation and corticosteroids in these patients could lead to a significant GI bleed [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the outcomes of GIB in COVID-19 patients differ from non-COVID-19 patients. This difference is recorded in the stay in the intensive care units (ICU), in the use of corticosteroid drugs, intubation, as well as in the causes of death, as these mainly concern the respiratory due to the COVID-19 infection [ 88 , 89 , 90 ]. No differences are observed in hemoglobin, in the administration of blood and crystalloid solutions, and the rate of rebleeding.…”
Section: Discussionmentioning
confidence: 99%
“…No differences are observed in hemoglobin, in the administration of blood and crystalloid solutions, and the rate of rebleeding. Also, the etiology of the bleeding and its clinical findings do not differ [ 89 , 90 ]. Finally, during the period of COVID-19, a significant decrease was observed in the number of patients coming to the hospital with GIB, which is attributed to their unwillingness to visit the hospital, due to COVID-19 [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors may increase the risk of bleeding and subsequent mortality in patients with UGIB. Furthermore, the COVID-19 pandemic may have interrupted healthcare systems, resulting in delayed or inadequate care for patients with UGIB [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%